Analysis of Pulp Molding Machine Selection Decision with the Application of Integration of the Ahp and Topsis Methods Case Study: Packaging Manufacturing Industry Company in Karawang - Falahal Majid; Husni Amani; Luciana Andrawina; Ilma Mufidah (Eduvest - Journal of Universal Studies, 2025)
In new product development, the selection of production machines is one very important part because it will greatly affect the success of product development. PT X is a company engaged in the packaging manufacturing industry. Currently PT X is developing biodegradable packaging products that meet food grade standards. In this project's case study, there are four engine brands that will be considered for selection. This study aims to determine priority criteria and the best alternative Pulp Molding machine. This study integrates the AHP method with TOPSIS. The AHP method is used to weight assessment criteria supported by the use of Super Decisions software, while the TOPSIS method is applied to sort the ranking of alternative machines. This study succeeded in determining the most important criteria in determining the choice of engine, in this case the production capacity with a weight of 0.395, while the best alternative machine to choose is JKE with a preference value of 0,503. Thus, this research can contribute to PT X in determining the choice of Pulp Molding machine.